TINJAUAN TEORI FEMINISME LIBERAL TERHADAP TRADISI LAMARAN GANJURAN DI DESA MAYONG KABUPATEN LAMONGAN - Mukhamad Bagus Irawan; Durratul Fu'adatus Sallimah; Azzahra Putri Affandi; Muhammad Jazil Rifqi (Familia: Jurnal Hukum Keluarga, 2025)
The tradition of proposing ganjuran is a tradition of proposing marriage carried out by women. This tradition is carried out by women because it is seen as a form of respect for men. However, this tradition is often considered to have deviations from the concept of gender equality. Therefore, this research will examine in more depth whether the practice of applying for ganjuran carried out by women is in line with the principles of gender equality promoted by liberal feminism. This research aims to analyze the tradition of ganjuran proposals in Mayong Village, Lamongan Regency through the lens of liberal feminist theory. Using qualitative methods, this research will explore the meaning of each stage in the ganjuran proposal tradition, and analyze how this tradition influences the position and role of women in society. The results of the research show that the ganjuran tradition reflects more progressive social change, namely a shift in patrilineal norms in Mayong Village society as in liberal feminist theory. The existence of the ganjuran tradition shows that women can be active in public spaces, especially in determining their life partner and by referring to liberal feminism it can be a tool to encourage gender equality in the Mayong Village community.